The Dominant factor of metabolic syndrome among office workers - Rahma Listyandini; Fenti Dewi Pertiwi; Dian Puspa Riana; Widya Asih Lestari (Journal of Health Science and Prevention, 2021)
The prevalence of metabolic syndrome in workers is high. Its impact can lower health status and disrupt work productivity. This research aimed to identify the dominant factor of metabolic syndrome among workers in government agencies of the Tanjung Priok port, Jakarta. The research method used descriptive- analytic with a cross-sectional design. The study used secondary data from medical check-up records of 256 workers in Port of Tanjung Priok. The inclusion criteria was all employees who had a medical check-up. Exclusion criteria was pregnancy and individuals with too much missing or poorly recorded information. The chi-square test and binary logistic regression were applied for analysis. The study found that metabolic syndrome prevalence was quite high in workers (38.7%). The results of a multivariate analysis showed physical activity (p = 0,003, OR = 2,238), total energy (P = 0,038, OR = 1,960), and carbohydrate intake (p = 0,014, OR = 0,490), together became the risk factor of the metabolic syndrome among workers. The dominant factor of metabolic syndrome was physical activity. The worker was susceptible to low physical activity so that the risk of metabolic syndrome was quite high. The company should improve the health promotion program in the workplace with regular screening, improved physical activity and provide a healthy meal to prevent metabolic syndrome in workers.